1988
DOI: 10.1590/s0036-46651988000400002
|View full text |Cite
|
Sign up to set email alerts
|

Emprego da exsangüineotransfusão em acidente loxoscélico humano, grave

Abstract: RESUMOFoi utilizada a exsangüineotransfusão, associada à soroterapia heteróloga específica e alcalinização urinaria, em um caso de acidente loxoscélico humano na cidade de São Paulo. A indicação da exsangüineotransfusão foi a intensa hemólise associada à gravidade e o iminente risco de morte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…En caso de hemólisis severa y CID, están indicadas la exanguineo-transfusión y la plasmaféresis para reponer los glóbulos rojos hemolizados y para remover los factores inflamatorios y procoagulantes en el plasma (Manríquez & Silva, 2009). Aunque la evidencia es baja, hay reportes de casos en favor de estas terapias (Silva et al, 1988;Said et al, 2014;Abraham et al, 2015).…”
Section: Tratamientounclassified
“…En caso de hemólisis severa y CID, están indicadas la exanguineo-transfusión y la plasmaféresis para reponer los glóbulos rojos hemolizados y para remover los factores inflamatorios y procoagulantes en el plasma (Manríquez & Silva, 2009). Aunque la evidencia es baja, hay reportes de casos en favor de estas terapias (Silva et al, 1988;Said et al, 2014;Abraham et al, 2015).…”
Section: Tratamientounclassified
“…In some cases, as that reported by [10], the surgical removal of dermatonecrotic lesion was essential for the recovery of a dog with loxoscelism. A report made by [19] described the utilization of blood transfusion in a case of loxoscelism in a human being to sooth the hemolysis situation. In addition, in another case report with a human being, Frezza [20] showed that the physical therapy after a repair surgery of dermatonecrotic lesions caused by a brown spider can help recover the amplitude of movements of the affected site.…”
Section: Loxoscelismmentioning
confidence: 99%